Ocular trauma among children in western Nepal: agents of trauma and visual outcome - Adhikari, RK; Pokhrel, H; Chaudhary, H; Chaudhary, B (Nepalese Journal of Ophthalmology, 2010)
DOI: 10.3126/nepjoph.v2i2.3726 Nep J Oph 2010;2(2) 164-165